"Hormonas de crecimiento vegetativo (ácido gibrelico, ecklona maxima) en injertos de guanabana (Ammona murricata L.) - Velásquez Andrade, Esperanza Nereida (2017)
The present investigation was carried out in the Teaching Program of vermiculture of the Experimental Campus "La María", belonging to the State Technical University of Quevedo, which is located in the canton Mocache, at Km 7 of the Quevedo - El Empalme, Province of Los Ríos, the objective of this research work was to evaluate the effect of the vegetative growth hormones Gibberellic Acid and Ecklonia maximum on the vegetative development in soursop (Annona muricata L) grafts, whose purpose is to increase the percentage of Soursop grafts improving their agronomic characteristics which are suitable for sale, for the realization of this research a completely randomized design was used with five treatments, gibberellic acid and maximum ecklonia and three repetitions, agronomic variables were measured as; Graft yield percentage, bud diameter, total height of shoots, total number of buds, number of leaves and an economic analysis per treatment. Treatment three whose application dose was Ecklonia maximum 5ml / L of water obtained 100% of spplants grafting, in the same way for the variable diameter of the buds it obtained values of 3.20 mm surpassing the control and the Other doses evaluated, in the variable total height of the outbreaks, the applied dose of Ecklonia maximum 5ml / L of water obtained values of 23.13 cm in comparison with the control and the doses evaluated, likewise in the variables of total number of buds and leaves treatment three composed of Ecklonia maximum 5ml / L of water obtained the highest values compared to the other treatments evaluated, for economic analysis, the best B / C ratio was obtained from treatment three with a value of 1.60 and a profit of $ 24 surpassing most of the other treatments studied. Keywords: hormones, grafts, agronomic, maximum Ecklonia